The Presidents’ Tales. Storytelling and Biographical Stories in the Case of Pedro Pablo Kuczynski - Mackelmann, Mathias (2017)
The following article analyzes the use of storytelling and biographical stories as elements of communication by presidential governments in Peru. It emphasizes Pedro Pablo Kuczynski administration. It briefly refers to the storytelling techniques used during the campaign that led to his election and then focuses mainly on the storytelling process during his current administration. The different strategies used are discussed in detail, analyzing whether they represent a successful formula to communicate with citizens and maintain a good government image. Finally, the article addresses external political factors that could radically change the population’s perception.